2010
DOI: 10.1097/gme.0b013e3181c8f4e1
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of metabolic syndrome in Chinese postmenopausal women and the optimum body composition indices to predict it

Abstract: The prevalence of MetS in Chinese postmenopausal women is 33.7%. Body composition indices (WC > or = 80.75 cm, BF > or = 36.695%, sagittal abdominal diameter > or = 18.35 cm, or BMI > or = 24.835 kg/m) were discovered to predict MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
29
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 21 publications
8
29
2
1
Order By: Relevance
“…However, the prevalence of MS in our study (21.7%) was lower than that reported from an earlier study in China. In the study of 181 postmenopausal women conducted in 2006-2008, the prevalence of MS was 33.7% [9]. Variation in the prevalence of MS could be due to heterogeneity of population characteristics such as age distribution, socioeconomic status or nutritional status, or due to different genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevalence of MS in our study (21.7%) was lower than that reported from an earlier study in China. In the study of 181 postmenopausal women conducted in 2006-2008, the prevalence of MS was 33.7% [9]. Variation in the prevalence of MS could be due to heterogeneity of population characteristics such as age distribution, socioeconomic status or nutritional status, or due to different genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…19,22 Some studies also have reported that the prevalence of IR increased in postmenopausal women. 12,13,20,23,24 In addition, Dorum et al 21 revealed that bilateral oophorectomy before 50 years was significantly associated with T2DM and metabolic syndrome. 21 In animal studies, ovariectomy was associated with an increased risk of diabetes, whereas estrogen administration protected against diabetes and increased the insulin response to glucose.…”
mentioning
confidence: 97%
“…[13][14][15][16][17][18] In this study, the waist circumference in postmenopausal women was higher than that of premenopausal women and result was statistically non signi cant. Similar types of observations were found by other workers.…”
Section: Discussionmentioning
confidence: 97%